2020
DOI: 10.1002/pra2.241
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of LIS research topics and methods from 2006 to 2018: A content analysis

Abstract: Replicating a series of studies of LIS research trends performed by Järvelin and colleagues, this content analysis systematically examines the evolution and distribution of LIS research topics and methods at six‐year increments from 2006 to 2018. Bibliographic data was collected for 3,422 articles published in LIS journals for the years of 2006, 2012, and 2018. Using a conceptual research strategy, the researchers identified the central research topics and research method for each article. The findings indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Ma and Lund (2020) found that in LIS, experiment was the most popular method in 2006, 2012 and 2018 with a share of about 30%. The second in popularity was survey.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ma and Lund (2020) found that in LIS, experiment was the most popular method in 2006, 2012 and 2018 with a share of about 30%. The second in popularity was survey.…”
Section: Methodsmentioning
confidence: 99%
“…Next, we will present studies which have analyzed LIS research after 2014. Ma and Lund (2020) is the only study using content analysis to explore the evolution of LIS. They analyzed the topics and methods of scholarly articles in 31 major LIS journals in 2006, 2012 and 2018, using categorizations of Tuomaala et al (2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Data science has grown in interest at a rapid rate in recent years, including within the discipline of information science. Just in the past five years, the number of articles relating to data topics published in information science journals has grown by nearly eight-fold (Ma & Lund, 2020;Virkus & Garoufallou, 2019). Ongoing efforts are pushing for a great intwining of data science with information science, as evident in the work of authors like Wang (2018), Poole (2021), Washington Durr (2020), andChohdary et al (2021) Bias in the analysis of data has long been a concern of analysts, though, until recent years, the focus was mainly on issues with the collection of data, the bias of the analysts themselves, and the imperfection of statistical models to reveal desired findings (Haussler, 1988;Kiviet, 1995;Mark, Eyssell, & Campbell, 1999).…”
Section: Reviewmentioning
confidence: 99%
“…Because information is inherent to every discipline of research, Bates (1999) referred to information science as a meta-field. Empirical investigations of LIS have highlighted its multidisciplinary nature (Aharony, 2012;Chua & Yang, 2008;Onyancha, 2018;Paul-Hus et al, 2016), as well as the gradual shift of the field's focus from libraries to a more diverse range of topics such as information technologies, knowledge management, and bibliometrics (Chua & Yang, 2008;Figuerola et al, 2017;Larivière et al, 2012;Ma & Lund, 2020;Onyancha, 2018). yet these previous studies all suffer from the same limitation: despite acknowledging the multidisciplinary nature of the field, they tend to ignore the differences in publication practices that characterize the disciplines composing the field and the potential biases that may result from these differences.…”
Section: Introductionmentioning
confidence: 99%